Biases in Capital Market Instrument Investing Decisions: A Study from India - Sakshi Agarwal; Saurabh Singh (Australasian Accounting, Business and Finance Journal, 2024)
This study examines the influence of different behavioral biases on the investment choices made by individual investors in the Indian capital market. The study utilizes a cross-sectional design, which entails gathering a substantial amount of data at a specific point in time. The study employed a survey methodology to collect data from a sample of 497 individual investors using purposive and snowball sampling. The data was collected using structural equation modeling (SEM), utilizing SPSS version 25 and AMOS version 26 as statistical software. This study characterizes individual investors as displaying irrational conduct. The study reveals a significant and positive association between representativeness, anchoring, and loss aversion biases and the investment decision-making process of individual investors in India. This study will enhance the current corpus of literature by examining the field of behavioral finance, which is gaining acknowledgment. Furthermore, few researchers have specifically examined these biases in developing countries, such as India.
Keywords: Behavioural Biases; Investment decision-making; SPSS; AMOS; Structural equation modeling